Fear of Aging: Apa yang Terjadi pada Ibu Single Parents Usia Dewasa Madya? - Sukma Nurmala (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2019)
This study aims to find out the fear of aging’s image on middle-age single parent mother. The approach employed in this study was qualitative phenomenological. Samples in this study as many as three respondents, single parents mother, have children, and working. The research subjects were 3 single parent mothers who were in the span of 40-59 years. Determination of research subjects using non-probability sampling with purposive sampling technique. The techniques of collecting data is observation and interview. Forms interviews used in this study are semi-structured interview types and using non-participant observation. The validity of the data in this study using triangulation of sources. The study found that fear of loss aspect is the most prominent at single parent mothers than fear of old people, psychological concerns, and physical appearance aspect. Fear of loss aspect at middle-aged single parent mother described from the subject’s fear of loss their children, strength and health of the body and loss of self-confidence.